Impact of L-Citrulline on Lipid Profile and Inflammatory Markers in Mice with Diet-Induced Atherosclerosis - Zainab Abdlkadhim Aboshnin (International Journal of Biomedicine)
Background: Lipid profile is the primary indicator of atherosclerosis disorder. Several strategies and therapeutic agents are targeted to reduce the risk of atherosclerosis by manipulating the lipid profile and inflammatory mediators. This study aimed to investigate the effect of citrulline on atherosclerosis and inflammation. Methods and Results: Eighteen adult male mice were assigned randomly for the following groups (six mice for each group): the control group, which received a standard chow diet; the induced group, which received a chow diet rich with 5% cholesterol; the L-citrulline-treated group, which received a chow diet rich with cholesterol, 5% together with 100 mg/kg of citrulline. The study lasted for ten weeks; the mice monitoring continued during and after completing the study course. After ten weeks of experiments, the blood sample was collected from the animals and centrifuged at 1500rpm for 15 minutes to obtain the serum. The ELISA technique was used to measure the level of TNF-α and ET-1. TC, HDL-C, LDL-C, VLDL-C, and TG were evaluated using the colorimetric enzymatic method and the Friedewald equation. The lipid profile components and inflammatory markers were similar at the baseline in the study groups. After ten weeks, the group of mice that received a cholesterol-rich diet showed a significant increase in all lipid profile components, excluding HDL-C, and the level of the inflammatory markers (ET-1 and TNF-α) compared with control mice. In the citrulline-treated group, the blood levels of TC, VLDL-C, LDL-C, and TNF-α were lowered insignificantly compared to the cholesterol-rich diet group. At the same time, in the citrulline-treated group, the levels of TG and ET-1 decreased significantly, and the HDL-C level increased compared to the cholesterol-rich diet group. Conclusion: A 10-week intake of L-citrulline against the background of a cholesterol-rich diet reduces the blood TG level and proinflammatory marker (ET-1) in experimental mice. L-citrulline use may have clinical benefits in the treatment of atherosclerosis in humans.